Sub-Module Voltage Estimation of Modular Multilevel Converter in PV Applications Using a Sliding Mode Observer - Imane alia; Imad Merzouk; Mehamed Mounir Rezaoui (ITEGAM-JETIA)
This paper presents a Sliding Mode Observer (SMO) for estimating sub-module (SM) voltages in Modular Multilevel Converters (MMCs) used in photovoltaic (PV) applications. MMCs are widely favored in medium- and high-voltage applications due to their modularity and scalability. However, traditional voltage sensing methods require numerous sensors, increasing system complexity, cost, and susceptibility to sensor failures. The proposed SMO offers a robust alternative, providing accurate voltage estimation despite parameter variations and external disturbances. The design and implementation of the SMO, along with its integration into the MMC control strategy, are demonstrated. The observer performance is validated through simulations and Matlab results, which demonstrate effective voltage estimation across different operating conditions. This method improves SM capacitor voltage balancing, enhances the reliable operation of MMCs in PV applications, and lowers costs.